FUNGSI ALTERNATIF ASAP HASIL PEMBAKARAN MATERIAL TUMBUHAN SEBAGAI EXOGENUS GROWTH FACTOR - Basry Yadi Tang (Partner, 2019)
In general, people throughout the world have utilized the application of smoke and/or fire from burning in terms of land cultivation, seed and food preservation and pest control. In Indonesia, most studies are still examining the application or use of combustion smoke in relation to seed storage time and pest control. While those who focus their studies on promoting growth and development are still very minimal. Therefore in this paper the author wants to review the alternative function of liquid smoke as an exogonus growth factor that can promote germination during the vegetative phase. Several studies have proven that the chemical compounds contained in the smoke from the combustion of plant materials that can be converted into liquid form (liquid smoke) can actually act as an external growth factor that can encourage plant growth and development, including germination.Key Words:  liquid smoke, Growth Factor external, Germination